1998
DOI: 10.1177/095632029800900306
|View full text |Cite
|
Sign up to set email alerts
|

Specific Inhibition of Influenza Virus RNA Polymerase and Nucleoprotein Gene Expression by Liposomally Encapsulated Antisense Phosphorothioate Oligonucleotides in MDCK Cells

Abstract: We have demonstrated that antisense phosphorothioate oligonucleotides (S-ODNs) inhibit influenza A virus replication in MDCK cells. Liposomally encapsulated and free antisense S-ODNs with four target sites (PB1, PB2, PA and NP genes) were tested for their abilities to inhibit virus-induced cytopathogenic effects in a MTT assay using MDCK cells. The liposomally encapsulated S-ODN complementary to the site around the PB2 AUG initiation codon showed highly inhibitory effects. In contrast, the inhibitory effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 52 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…They are potentially useful therapeutic agents for the treatment of viral diseases [13]. AS ODNs are effective against the influenza virus in vitro and in vivo by targeting the PA, PB2, NS1 and PB1 genes; these target sites are mainly focused on the conserved AUG initiation codon of the influenza virus [14][15][16][17]. There are no current studies of AS ODNs on the NP gene of H5N1 avian influenza.…”
Section: Introductionmentioning
confidence: 98%
“…They are potentially useful therapeutic agents for the treatment of viral diseases [13]. AS ODNs are effective against the influenza virus in vitro and in vivo by targeting the PA, PB2, NS1 and PB1 genes; these target sites are mainly focused on the conserved AUG initiation codon of the influenza virus [14][15][16][17]. There are no current studies of AS ODNs on the NP gene of H5N1 avian influenza.…”
Section: Introductionmentioning
confidence: 98%
“…Because our data indicated that antisense phosphothioate oligonucleotides targeting AUG initiation codon sequences of PB2 mRNA effectively inhibited the influenza virus RNA polymerase activity [9–11], and influenza virus replication in infected cells [12–14] and mice [15], we tested the DNA enzyme which carries 10‐23 catalytic sequence flanked with complementary sequences around the AUG initiation codon of PB2 mRNA (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…To date, the application of antisense phosphothioate oligonucleotides to inhibit the replication of various viruses has been of great success [1]. We have demonstrated that liposome‐encapsulated antisense phosphothioate oligonucleotides complementary to PB2‐AUG and PA‐AUG initiation codons inhibited the influenza virus RNA polymerase activity [9–11], and influenza virus replication in MDCK cells [12–14] and in mice [15]. In this paper, we describe the inhibition of influenza virus replication in cultured cells by RNA‐cleaving DNA enzyme which was designed from 10‐23 catalytic motif targeting the PB2‐AUG initiation codon, and compare the results with those for antisense phosphothioate oligonucleotides complementary to the same position [15].…”
Section: Introductionmentioning
confidence: 99%
“…An antisense phosphorothioate oligonucleotide directed against the initiation codon of the influenza virus PB2 mRNA has been shown to inhibit virus replication in MDCK cells in a sequence specific manner, with an IC so of 0.15 11M when encapsulated in cationic liposomes. Free oligonucleotides could interfere with virus attachment in a sequence independent manner, with ICsos between 1 and 311M [45]. Protective efficacy of a liposomal preparation was also demonstrated in the mouse model after intravenous administration of 40 mg/kg twice daily for 5 days.…”
Section: Inhibition Of Viral Replicationmentioning
confidence: 96%